An Empirical Analysis of East Asia's Pre-crisis Daily Exchange Rates - Joseph Dennis Alba; Donghyun Park (Asian Development Bank (ADB), 2007)
"Joseph Dennis Alba and Donghyun Park write that the exchange rate peg to the United States dollar is widely believed to have been a major cause of the Asian financial crisis of 1997–1998. Rigid exchange rates may have invited massive capital inflows into East Asia by creating a false sense of security among investors. A substantial empirical literature examines the actual behavior of pre-crisis exchange rates in the region. The authors seek to contribute to this literature by using daily data compared to other studies that tend to use monthly data and other lowerfrequency data."
hdl:11540/1866
Keywords: 330; Wechselkurs; US-Dollar; Währung; Ostasien; ARCH-Modell